Anti-DFS70 antibodies in systemic lupus erythematosus: Prevalence in a large Chinese cohort and an unexpected association with anti-dsDNA antibodies by a long-term follow-up - Dai, Yingxin; Li, Enling; Chen, Dandan; Niu, Xiangyu; Wang, Zhiqing; Lu, Liangjing; Zheng, Bing (Frontiers in Immunology, 2022)
Objective Monospecific autoantibodies to dense fine speckles 70 (DFS70) antigen are purported to aid in excluding systemic autoimmune rheumatic diseases (SARD) such as systemic lupus erythematosus (SLE). However, the non-isolated anti-DFS70 still has a certain prevalence in SLE patients, and the clinical significance remains unclear. We aimed to investigate the prevalence, clinical relevance, and value of long-term monitoring of anti-DFS70 antibodies in SLE patients. Methods Anti-DFS70 antibodies were measured by enzyme-linked immunosorbent assay (ELISA) in 851 SLE patients, 211 healthy individuals, and 194 patients with other SARD (except SLE). Demographic, serological, and clinical associations of anti-DFS70 antibodies were analyzed by a stepwise multivariable logistic regression model. The correlation of anti-DFS70 with anti-dsDNA, anti-C1q, and SLE Disease Activity Index 2000 (SLEDAI-2K) was analyzed. Sixty-one SLE patients with follow-up time ranging from 2 to 57 months were measured anti-DFS70 antibodies using both ELISA and line immunoassay. The dynamic variations of anti-DFS70 antibodies were evaluated with anti-dsDNA, anti-C1q, and SLEDAI-2K during the follow-up. Results The prevalence of anti-DFS70 was significantly higher in SLE (20.7% (176/851)) than in healthy individuals (9.5% (20/211), p = 0.0002) and other SARD (10.8% (21/194), p = 0.002). Multivariable analysis revealed that anti-DFS70-positive SLE patients were associated with younger age (odds ratio (OR) = 0.982; 95% confidence interval (CI) = 0.969, 0.995), higher frequencies of anti-dsDNA (OR 1.598; 95% CI 1.107, 2.306) and anti-PCNA (OR 6.101; 95% CI 2.534, 14.688), and higher levels of serum IgG (OR 1.097; 95% CI 1.067, 1.129) and were more likely to be accompanied by mucosal ulcers (OR 5.921; 95% CI 1.652, 21.215). The O.D. value of anti-DFS70 positively correlated with levels of anti-dsDNA (r = 0.183, p < 0.0001) and anti-C1q (r = 0.181, p < 0.0001), respectively, but not with SLEDAI-2K (p = 0.920). During the follow-up, 49 (42 negative and 7 positive) patients remained stable with anti-DFS70 levels. The other 12 patients experienced significant changes in anti-DFS70, and 83.3% (10/12) of them showed similar trends between anti-DFS70 and anti-dsDNA by evaluation of dynamic variations. Conclusion Anti-DFS70 antibodies seem to be prevalent in Chinese SLE patients. The positive association of anti-DFS70 with anti-dsDNA and consistent dynamic variation between anti-DFS70 and anti-dsDNA during the follow-up suggested a potential relationship between anti-DFS70 and anti-dsDNA in patients with SLE.